Development of Extreme Addition Mathematics Media to Improve Counting Skills of Madrasah Ibtidaiyah Students - Anwar, Choirul; Susapti, Peni; Himmah, Wulan Izzatul (UIN Sunan Kalijaga Yogyakarta, 2025)
Low numeracy skills remain a persistent challenge in primary education, particularly in Madrasah Ibtidaiyah (MI), where students often struggle with basic arithmetic operations such as addition. This study aims to develop Extreme Addition Mathematics media to enhance the counting skills of fourth-grade Madrasah Ibtidaiyah (MI) students and evaluate its effectiveness. The research employed the Research and Development (R&D) method, guided by the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The media was validated by material, media, and learning experts using Aiken's V coefficient, with results of 0.87 (material), 0.91 (media), and 0.89 (learning), all exceeding the 0.75 threshold, confirming its validity. Implementation involved 57 students divided into an experimental group (n=29) using the media and a control group (n=28) with conventional methods. Pretest and posttest data were analysed using Shapiro-Wilk normality tests, Levene's homogeneity test, and independent t-tests. The experimental group showed a significant improvement, with posttest scores increasing from 40.72 to 86.90, compared to the control group's 49.40 to 72.79. The N-Gain score for the experimental group was 77.4%, categorised as